The Effect of Aeration on The Growth and Production of Lettuce (Lactuca sativa L.) Using the Floating Raft Hydroponic System - Dharmayanti , Ni Kadek Sri Arini; Sumiyati; Yulianti , Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The floating raft hydroponic system is one of the cultivationtechniquesto obtain a more controlled environmentfor plant. However, this system has a drawback which is lack of dissolved oxygen leading to root rot. This issue is overcome by providingaeration. This study aims to determine the effect of aeration on lettuce cultivation with a floating raft hydroponic system. The study used a randomized block design (RAK) with 4 treatments, namely a floating raft hydroponic system that was not given any aerator as a control (P0), a floating raft hydroponic systemthatwas givenan aerator with a flow rate of 700 liters/hour(P1); the floating rafthydroponic systemthat was given an aerator with a flow rate of 1500 liters/hour (P2), and a floating raft hydroponic system that was givenan aerator with a flow rate of 2000 liters/hour P3 and each treatment was repeated 4 times. The results showed P3 had a significant effect on changes in dissolved oxygen, the number of leaves, leaf width, root length, fresh weight, dry weight and leaf color. The P3 gave the best results among all other treatmentswith an average value of dissolved oxygen of 8.4 mg / L, the number of leaves 17.6, the value of leaf blade width 8.10, the value of root length29.70 cm, the value of shoot fresh weight 207.12, the value of the dry weight of the canopy 4.96, and the value of the leaf color is 48.31.